Ekonomi Bayangan Dalam Novel Pulang Karya Tere Liye Berdasarkan Teori Konspirasi - Andika Hendra Mustaqim (Wanastra: Jurnal Bahasa dan Sastra, 2015)
The aim of this research is explore the shadow economy in the Pulang which written by Tere Liye. The novel is analyzed by using content analysis to find evidence and criticism on shadow economy and conspiracy. The research finds shadow economy is the main theme of the novel. Tere Liye defines very clearly the shadow economy and conveys to the reader that the shadow economy has become part of the world community, especially Indonesia. Not only that, the shadow economy has also taken root. Moreover, conspiracy became focus on the novel, From the beginning of the novel, conspiration will destroy and seize power Tong Family. Bashir is first conspirator.Based on the conspiracy theory, the researcher found the real conspirator in the novel was Bujang because Bujang acquired the Tong family. He also wants to take over leadership of the Tong family.